Analisis Pola Asuh Orang Tua Terhadap Preventif Stunting Pada Anak Usia Dini Di Paud BKB Kemas Nur Qolbu Kota Serang - Nina Herlina; Inten Risana; Havid Surya; Ratu Yustika Rini (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Stunting is a chronic nutritional problem that significantly affects children's physical and cognitive development. One of the crucial factors in preventing stunting is parenting style. This study aims to analyze how parenting patterns contribute to preventive efforts against stunting in early childhood at PAUD BKB Kemas Nur Qolbu Serang. This research employs a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation involving parents and educators at the institution. Data analysis was conducted through stages of open coding, axial coding, and selective coding. The results reveal that parenting in the context of stunting prevention involves four main aspects: (1) fostering healthy and balanced eating habits; (2) emphasizing hygiene and environmental sanitation; (3) parental involvement in monitoring children's growth and development; and (4) maintaining responsive and supportive communication with children. The findings suggest that a democratic parenting style, characterized by consistent supervision and care, plays a significant role in reducing the risk of stunting. This study implies that continuous education and assistance for parents are essential in shaping healthy parenting behaviors that support optimal child development. Therefore, strong collaboration between families, educators, and health institutions is vital in the early prevention of stunting